Cerenkov luminescence imaging guided selective-reconstruction for a flexible dual-head PET. (7th April 2017) - Yang, D.; Chen, X.; Zhang, C.; Wan, L.; Meng, F.; Xie, Q.; Liang, J.
Abstract: Dual-head PET can simply and flexibilly adjust its architecture to fit the size of the imaging object, making it great potential for simultaneous multi-modality molecular imaging. In this paper, we proposed conceptally dual-modality imaging system of distance-adjustable dual-head PET and Cerenkov luminescence imaging (CLI), and implemented a CLI guided selective-reconstruction method. In the selective-reconstruction, we reconstructed the information inside a predefined region of interest using a fine voxel, whereas reconstructed other regions using a coarse voxel. We used CLI data as a priori information to outline the predefined region of interest. Simultaneously, for reducing the computaion burden, an attenuation map with a coarse voxel size was used for the attenuation correction. We demonstrated the feasibility and effectiveness of our proposed method with Monte Carlo based simulations by reconstructing phantom consisted of two hot rods. Experiment results show that an most improved efficiency over 70 times speedup with an MSE of 5.2235.